2018
DOI: 10.3390/nu11010032
|View full text |Cite
|
Sign up to set email alerts
|

Olive Oil Effects on Colorectal Cancer

Abstract: Colorectal cancer is the fourth cause of cancer-related death worldwide. A Mediterranean diet showed protective action against colorectal cancer due to the intake of different substances. Olive oil is a fundamental component of the Mediterranean diet. Olive oil is rich in high-value health compounds (such as monounsaturated free fatty acids, squalene, phytosterols, and phenols). Phenolic compounds exert favourable effects on free radicals, inflammation, gut microbiota, and carcinogenesis. The interaction betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 106 publications
3
66
0
Order By: Relevance
“…EVOO polyphenols fit this picture, presenting qualities of medical interest including anti‐inflammatory and immune‐modulatory activities, only partially related to their antioxidant power, which could be useful in the management of skin diseases . In this regard, a polyphenol‐based cosmeceutical containing olive polyphenol extract, exhibited positive skin effects .…”
Section: Discussionmentioning
confidence: 99%
“…EVOO polyphenols fit this picture, presenting qualities of medical interest including anti‐inflammatory and immune‐modulatory activities, only partially related to their antioxidant power, which could be useful in the management of skin diseases . In this regard, a polyphenol‐based cosmeceutical containing olive polyphenol extract, exhibited positive skin effects .…”
Section: Discussionmentioning
confidence: 99%
“…34,35 In addition, the Moroccan population has preserved some traditionally processed meats such as Khlii meat in olive oil, which are rich in compounds that might be directly relevant for CRC prevention (such as monounsaturated fatty acids, squalene, phytosterols and phenols) or could modulate the composition or microbial activity of the colon, with a possible role in cancer prevention. 36 In addition, the cooking of traditionally processed meat at low temperatures could also prevent the formation of HCAs and PAHs and other carcinogenic compounds, which are formed when meat is cooked at high temperatures. 33,37 A positive association was observed between industrially processed meat and colon, rectal and CRC risk.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported to inhibit proliferation, migration, and invasion of both breast and prostate cancer cells via inhibition of c‐Met phosphorylation (Elnagar, Sylvester, & El Sayed, ). Recently, various in vitro studies have suggested that olive oils can exert chemopreventive effects against various types of human carcinoma cells such as prostate cancer, colon cancer, leukemia, and breast cancer (Borzi et al, ; Fabiani et al, ; Fabiani et al, ; Han, Talorete, Yamada, & Isoda, ; Hashim et al, ). Olive oil inhibits cell cycle progression, cell proliferation, induces oxidative stress, and apoptosis and stimulates the immune system, thereby preventing carcinogenesis.…”
Section: Some Common Phytochemicals With Chemopreventive and Chemothementioning
confidence: 99%
“…Olive oils are the liquid fats obtained from olives and the most impor- Breslin, & Foster, 2015). It has also been reported to inhibit proliferation, migration, and invasion of both breast and prostate cancer cells via inhibition of c-Met phosphorylation (Elnagar, Sylvester, & El Sayed, 2011 (Borzi et al, 2018;Fabiani et al, 2006;Fabiani et al, 2008;Han, Talorete, Yamada, & Isoda, 2009;Hashim et al, 2008).…”
Section: Olive Oilsmentioning
confidence: 99%